“Olha, os bebês estão chegando!” O direito à Educação Infantil do Campo, das Águas e das Florestas: a creche no Assentamento Pirituba II do MST – SP - Araujo, Thaise Vieira de (Universidade Federal de São Carlos, 2025)
This thesis was developed in the research line “Training of Educators, Daily Life and Educational Practices”, linked to the Graduate Program in Education of the Federal University of São Carlos, Sorocaba campus, in the State of São Paulo. It is part of the Research Group on Children, Early Childhood Education and Childhood Studies – CRIEI, which is coordinated by Prof. Maria Walburga dos Santos. The theme focused here is part of the discussions on Early Childhood Education in the Countryside, Water and Forest areas. Thus, we took as a base the Terezinha de Moura Rodrigues Gomes Municipal School, located in the Pirituba II Settlement, in Itapeva, São Paulo state, for the development of the research. The general objective of the case study was to analyze the right of children from 0 to 3 years old to daycare in the countryside, considering both the public policies already implemented and those that still need to be established in guaranteeing the right to education. The research, with a qualitative approach, had the following main instruments for data construction: field research; participant observation; interviews with teachers, families, Early Childhood Education monitors and managers (school principal and pedagogical coordinator); field diary record; and photography. The information collected was organized based on themes that guided the research and that are connected to the general and specific objectives. The analysis took place from the theoretical framework of the research, that is, the contributions of the debates on Early Childhood Education in the Countryside, Water and Forest areas, in dialogue with Early Childhood Education and Rural Education. As a result, we found that the daycare center in the Pirituba II Settlement is the result of the organized political struggle of peasant women; the work of the School Director has been committed to the right of children, including babies, to Rural Education. There are favorable conditions for the offer of the daycare center, such as a newly built facility and a team of teaching and non-teaching professionals who have secure job contracts, avoiding turnover. However, demands were observed that indicate the continuity of the public policy, such as the provision of school transportation for the age group of 0 to 3 years; access to daycare for babies up to 6 months of age, if there is demand from families; teacher training and curriculum that consider the specificity of Early Childhood Education in the Countryside, Water and Forest areas, guaranteeing the rights of children in rural territories and the consolidation of an Education situated in and belonging to the Countryside in the investigated school.
“Look, the babies are coming!” The right to Early Childhood Education in the Countryside, about the Waters and about the Forests areas: The daycare center in the Pirituba II Settlement of the MST - SP
Keywords: Bebê; MST; Educação Infantil do Campo, das Águas e das Florestas; Babie; MST; Early Childhood Education of the Countryside, Water and Forest areas; CIENCIAS HUMANAS::EDUCACAO